2023
DOI: 10.7759/cureus.37180
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast Add-On Benefits Over Conventional Drugs (ABCD) in Unstable Non-segmental Vitiligo: A 12-Week Single-Center Randomized Controlled Trial

Abstract: BackgroundApremilast is an oral phosphodiesterase-4 enzyme inhibitor that modulates the immune system by increasing intracellular cyclic adenosine monophosphate levels and inhibiting inflammatory cytokines synthesis. We aimed to compare the efficacy and safety of add-on apremilast in combination therapy with standard treatment in patients with unstable, non-segmental vitiligo. MethodsThe study was a 12-week randomized, controlled, parallel-group, open-labeled trial. The control group received standard treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The time interval between the start of apremilast and the beginning of repigmentation was reported to be 4 weeks, and the reduction of Vitiligo Area Scoring Index (VASI) was 1.24. In the control group, the beginning of repigmentation was reported after 7 weeks, and the reduction of VASI was reported to be 0.05 19 . When comparing NB‐UVB therapy alone to the combination of NB‐UVB and Apremilast therapy, there were no significant differences found in the VASI score, Dermatology Life Quality Index, and visual analog scale scores 20 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The time interval between the start of apremilast and the beginning of repigmentation was reported to be 4 weeks, and the reduction of Vitiligo Area Scoring Index (VASI) was 1.24. In the control group, the beginning of repigmentation was reported after 7 weeks, and the reduction of VASI was reported to be 0.05 19 . When comparing NB‐UVB therapy alone to the combination of NB‐UVB and Apremilast therapy, there were no significant differences found in the VASI score, Dermatology Life Quality Index, and visual analog scale scores 20 .…”
Section: Resultsmentioning
confidence: 96%
“…Because of its ability to regulate the immune system and its positive safety record, apremilast is currently being studied as a potential treatment choice for various other inflammatory disorders 10,48 . In three out of the four studies we reviewed, the effectiveness of apremilast in treating vitiligo was confirmed, and no specific side effects were reported 10,19,21 . It is anticipated that this drug will become a widely used treatment option for vitiligo in the future.…”
Section: Discussionmentioning
confidence: 92%
“…However, the efficacy of apremilast, an oral PDE4 inhibitor, appears contradictory. While a phase 2 clinical trial involving 80 vitiligo patients ended up with no additional benefit when combined with conventional phototherapy, several studies have suggested that apremilast may potentiate phototherapy and halt disease progression, particularly advantageous to patients with darker skin 94 95 96 97 98 . There are few case reports supporting the use of crisaborole, a topical PDE4 inhibitor 99 100 .…”
Section: Phosphodiesterase Type 4 (Pde4)mentioning
confidence: 99%
“…Regarding apremilast, all selected studies utilize a dose of 30 mg twice daily [57][58][59][60][61][62]. In 2019, a case series [58] and a case report [57] showed the utility of apremilast in monotherapy in vitiligo.…”
Section: Phosphodiesterase 4 (Pde-4) Inhibitorsmentioning
confidence: 99%
“…Two clinical trials compared the improvement with the addition of apremilast to NB-UVB treatment with conflicting results [60,61]. Recently, Sharma et al [62] have reported an improved response of vitiligo after adding apremilast to standard treatment. In most studies, headache and gastrointestinal discomfort have been reported as the main adverse effects of the treatment.…”
Section: Phosphodiesterase 4 (Pde-4) Inhibitorsmentioning
confidence: 99%